ANALISIS PERBANDINGAN METODE PENYUSUTAN AKTIVA TETAP PADA PT UNO RITEL PAPUA - Alfrianti Palungan; Ahmad Tomu (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2018)
This research aims to determine the difference between the depreciation expense of depreciation method of fixed assets at PT Uno Retail papua and to determine which depreciation method should be used by PT Uno Retail Papua . This research is a comparative research. The data used are primary data in the form of interviews with resource persons and secondary in the form of corporate financial statements. Data collection techniques in this research is through interviews, documentation and heritage studies. To determine the difference between the depreciation expense of fixed assets at PT Uno Retail Papua is done by comparing the results of calculations using straight-line method, the method of the number of years, and the declining balance method. The result of this research showed that the burden of depreciation of fixed assets at PT Uno Retail in 2016 by using smaller straight-line method that is equal to Rp75.639.554 compared to the amount of depreciation expenses using the method of number of Rp130.123.539 the declining balance method is Rp151.279.137. The method that maximizes profit PT PT Uno Retail papua is a straight line method because with the use of the method then the profit earned is Rp68.003.369 compared to the method of the number of year numbers earned profit Rp20.329.882 or using a double declining balance method that earns only Rp1.818.734.